2018
DOI: 10.1088/1742-6596/1054/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

History and recent progress of QMG™ and QMG bulk magnets

Abstract: Abstract. The microstructure of QMG consists of a single crystal REBa 2 Cu 3 O x phase and fine RE 2 BaCuO 5 particles. Y-based QMG was first produced in 1988 by the Quench and Melt Growth method. A bulk magnet made from QMG was proposed in 1989. QMG bulk magnets were realized by enlargement technology using RE substitute seed crystals. Based on these technological innovations, the development of NMR and MDDS, which are product-based applications of bulk magnets, has recently been reported from the research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The reinforcement concept was, in fact, first proposed by Morita et al in 2017 for ring-shaped bulk magnets [16,17], where they demonstrated that the proposed structure significantly decreased the mechanical strains experienced by the superconductor and prevented crack formation. Furthermore, the resultant composite proposed here also benefits from improved thermal stability as a result of enhanced thermal capacitance and thermal conductivity, which helps to reduce the occurrence of flux jumps.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement concept was, in fact, first proposed by Morita et al in 2017 for ring-shaped bulk magnets [16,17], where they demonstrated that the proposed structure significantly decreased the mechanical strains experienced by the superconductor and prevented crack formation. Furthermore, the resultant composite proposed here also benefits from improved thermal stability as a result of enhanced thermal capacitance and thermal conductivity, which helps to reduce the occurrence of flux jumps.…”
Section: Introductionmentioning
confidence: 99%
“…A preferable approach is to construct the Bitter stack from discs of HTS bulk superconductor that allow current to be transferred directly across both top and bottom faces. Electromagnets comprising of spirally cut HTS bulk superconductors have previously been demonstrated [15][16][17], however there are no reports of using these materials in a Bitter-like bulk architecture.…”
Section: Introductionmentioning
confidence: 99%